Top-Down and Bottom-Up Contributions to Understanding Sentences Describing Objects in Motion - Rueschemeyer, Shirley-Ann; Glenberg, Arthur M.; Kaschak, Michael; Mueller, Karsten; Friederici, Angela (Frontiers in Psychology, 2010)
Theories of embodied language comprehension propose that the neural systems used for perception, action and emotion are also engaged during language comprehension. Consistent with these theories, behavioral studies have shown that the comprehension of language that describes motion is affected by simultaneously perceiving a moving stimulus (Kaschak et al., 2005). In two neuroimaging studies, we investigate whether comprehension of sentences describing moving objects activates brain areas known to support the visual perception of moving objects (i.e., area MT/V5). Our data indicate that MT/V5 is indeed selectively engaged by sentences describing objects in motion towards the comprehender compared to sentences describing visual scenes without motion. Moreover, these sentences activate areas along the cortical midline of the brain, known to be engaged when participants process self-referential information. The current data thus suggest that sentences describing situations with potential relevance to one’s own actions activate both higher-order visual cortex as well brain areas involved in processing information about the self. The data have consequences for embodied theories of language comprehension: first, they show that perceptual brain areas support sentential-semantic processing. Second the data indicate that sensory-motor simulation of events described through language are susceptible to top-down modulation of factors such as relevance of the described situation to the self.